PENDEKATAN KONSELING PASTORAL BERBASIS PSYCHODELSI DALAM DINAMIKA KELOMPOK TUMBUH BERSAMA: UPAYA MEMBANGUN KOMUNITAS YANG MENUMBUHKAN IMAN DI STTAM NIAS BARAT - Budieli Hia; Renungan Hulu; Irenis Waruwu; Febrianus Gulo (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2026)
This study explores the application of pastoral counseling within the dynamics of Growing Together Groups (Kelompok Tumbuh Bersama – KTB) as an effort to build a faith-nurturing community at the Anugerah Misi Theological Seminary (STTAM) West Nias. Using a qualitative descriptive approach, this research analyzes how pastoral counseling—particularly through the integration of the Psychodelsi model (Psycho, Deliverance, Spiritual)—can contribute to students’ spiritual growth and maturity. The study reveals that many theology students still carry unresolved emotional wounds, particularly anger toward their parents, which hinder their spiritual development. By employing pastoral counseling integrated with the Psychodelsi framework, students are guided through personal reflection (life story), psychological typology assessment, and spiritual deliverance to identify the roots of inner bitterness and to experience genuine forgiveness. The results indicate that the pastoral counseling process not only reduces emotional distress and anger but also leads to deeper spiritual renewal, reconciliation, and transformation of character. Furthermore, the integration of pastoral counseling principles within KTB strengthens community bonds, enhances accountability among members, and fosters an environment where faith can flourish through shared experiences of healing and discipleship. In conclusion, the study highlights that the Psychodelsi-based pastoral counseling approach provides a holistic and contextual framework for spiritual formation in theological education, making it an effective model for developing faith communities that embody Christlike maturity, compassion, and wholeness.